2022
DOI: 10.1038/s41598-022-10682-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of rice straw biochar on microbial community structure and metabolic function during anaerobic digestion

Abstract: Anaerobic digestion technology mitigates agricultural organic waste pollution, thereby alleviating the energy crisis. Biochar materials increase the utilisation rate of biomass resources and promote the enrichment and growth of microorganisms. Biochar is an effective exogenous additive that stabilises the anaerobic digestion, improves anaerobic digestion efficiency and gas production. Herein, biochar materials were prepared from rice straw utilising the sequencing batch anaerobic digestion process. The biochar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…That is opposite to the findings of (S. Wang et al, 2022), that added straw biochar (600°C for 20 min) at 7.1 g BC ×L -1 to the AD of cow dung. (S. Wang et al, 2022) also obtained methane production enhancement after biochar addition but this effect was due to an increase of hydrogenotrophic methanogens abundance, while acetoclastic methanogens such as Methanosaeta decreased massively (S. Wang et al, 2022). On the contrary results of (Masebinu et al, 2021) showed that for a well-working AD system without any severe disturbances, biochar does not improve methane production nor decrease it and microbial community composition is not altered.…”
Section: Vs -1contrasting
confidence: 91%
See 1 more Smart Citation
“…That is opposite to the findings of (S. Wang et al, 2022), that added straw biochar (600°C for 20 min) at 7.1 g BC ×L -1 to the AD of cow dung. (S. Wang et al, 2022) also obtained methane production enhancement after biochar addition but this effect was due to an increase of hydrogenotrophic methanogens abundance, while acetoclastic methanogens such as Methanosaeta decreased massively (S. Wang et al, 2022). On the contrary results of (Masebinu et al, 2021) showed that for a well-working AD system without any severe disturbances, biochar does not improve methane production nor decrease it and microbial community composition is not altered.…”
Section: Vs -1contrasting
confidence: 91%
“…Interestingly BC addition increased the abundance of acetoclastic methanogens that convert acetate (CH 3 COOH) to methane and carbon dioxide, while reducing the abundance of hydrogenotrophic methanogens that produce methane from hydrogen and CO 2 (Zhang et al, 2019). That is opposite to the findings of (S. Wang et al, 2022), that added straw biochar (600°C for 20 min) at 7.1 g BC ×L -1 to the AD of cow dung. (S. Wang et al, 2022) also obtained methane production enhancement after biochar addition but this effect was due to an increase of hydrogenotrophic methanogens abundance, while acetoclastic methanogens such as Methanosaeta decreased massively (S. Wang et al, 2022).…”
Section: Vs -1mentioning
confidence: 65%
“…It is important to highlight the connection between these issues, since the physicochemical and functional properties depend directly on optimizing the generation of value-added by-products obtained by applying AD. [ 11 , 41 , 63 , 64 ] The third subgroup is made up of the terms ‘co-digestion’ and ‘digestate’ and the fourth subgroup is made up of the word ‘sludge.’ As the groupings are smaller, they indicate that they are the areas where the application of BC is being explored, with co-AD being one of the most studied topics ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, based on the ash composition in biochar, putting it an anerobic digester can enhance the concentration of trace metals and alkalis, resulting in improved performance of the process (Pan et al, 2019b). Biochar's porous structure and surface area serves as a living environment for microorganisms (Wang et al, 2022). However, heating rate, reaction temperature, and feedstock all affect biochar characteristics, including the fixed carbon content, nutrient content and availability, cation exchange capabilities and pH (Ghodake et al, 2021).…”
Section: Biochar Characteristics 221 Physical Propertiesmentioning
confidence: 99%